Optical Absorbance Study of Carbon Nanomaterials Synthesized from Used-cooking Oil via Liquid-phase Exfoliation Using a Kitchen Blender in n-Hexane Solution - Lilis Misnawati; Wipsar Sunu Brams Dwandaru (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2017)
Abstract. UV-Visual (UV-Vis) optical absorbance study in the synthesis of carbon nanomaterials produced from used-cooking oil via liquid-phase exfoliation (LE) using a kitchen blender which is dissolved in n-hexane solvent has been conducted. Here, the blending time duration and solution concentration are varied, i.e. (in hours) 1, 2, and 3, and (in milimol/mL) 0.2, 0.4, and 0.6, respectively. The solutions obtained from this study are characterized using UV-Vis spectrophotometer. The experiment is carried out by directly blending used-cooking oil and then dissolving it in n-hexane solvent. A solution of pure cooking oil in n-hexane is used as a reference solution for the UV-Vis spectrophotometer. For variation of blending time duration, the UV-Vis results show a blue shift from 269.5 nm to 235.5 nm as the blending time is increased from 1 to 3 hours and indicate the presence of graphene oxide (GO) material. A second absorbance peaks at around 349 nm to 351 nm correspond to the occurrence of carbon quantum dot (CQD) material. Moreover, for the variation of solution concentrations, a red shift from 311.5 nm to 350 nm occurs as the solution concentration is increased from 0.2 to 0.6 milimol/mL. The red shift point towards an exfoliation of used-cooking oil from GO into CQD materials.Keywords: graphene oxide, carbon quantum dot, UV-Vis spectroscopy, liquid-phase exfoliation, used-cooking oil, n-hexane.